(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
Considering that the body is a central theme in different feminist debates, in this article I take the Brazilian case as a basis, carrying out a comparative analysis between two literary works: the book “Histórias de Tia Nastácia”, by Monteiro Lobato, and “Tudo Nela Brilha e Queima”, by Ryane Leão. I seek to articulate these readings and the concepts of images of control, self-definition and epistemicide. My purpose is to understand how images of control, used as a way to separate black women into stereotypes, serve to categorize them into three main categories: matriarchs, mules and sexually deviant women from a certain standard, and imprison them in a supposed corporeal destiny, while at the same time moving them away from a self-defined bodily experience. By comparing the two works in question, I intend to question the use of images of control in Brazilian literature, bringing to light one of the tools to combat epistemic racism, the potential of self-definition.